Regulation of Tripartite Motif-Containing Proteins on Immune Response and Viral Evasion - Zhang, Xiu-Zhong; Li, Fu-Huang; Wang, Xiao-Jia (Frontiers in Microbiology, 2021)
Tripartite motif-containing proteins (TRIMs), exhibiting ubiquitin E3 ligase activity, are involved in regulation of not only autophagy and apoptosis but also pyrotosis and antiviral immune responses of host cells. TRIMs play important roles in modulating signaling pathways of antiviral immune responses via type I interferon, NF-B, Janus kinase/signal transducer and activator of transcription (JAK/STAT), and Nrf2. However, viruses are able to antagonize TRIM activity or evenly utilize TRIMs for viral replication. This communication presents the current understanding of TRIMs exploited by viruses to evade host immune response.